Overview on Steady State Thermal Analysis of High Speed Gearbox - Ge Shixiang; Liu Zhilei; Wu Luji; Yang Linjie; Gang Haiming (Jixie chuandong)
The heat quantity generated by the working condition characteristic of high speed gearbox will lead to high temperature,and the high temperature especially local high temperature will make the lubricating condition badly,the contact and anti-scuffing strength of gear lower and the lubricating oil accelerated aging.Firstly,combining with the existing achievements at home and abroad,the mechanism of heat generating and transferring of the system and the determination of boundary condition are introduced. Then,the thermal network method,finite element simulation and test which widely applied at present are briefly introduced.